The devil's dictionary, tales, & memoirs - Bierce, Ambrose (Library of America, 2011)
A veteran of some of the bloodiest battles of the Civil War, Ambrose Bierce went on to become one of the darkest and most death haunted of American writers, the blackest of black humorists. This volume gathers the most celebrated and significant of Bierce's writings.